Implementasi Kebijakan Pusat Kesejahteraan Sosial Anak Integratif Di Kabupaten Jombang - Wafiq Ima Azizah; Tukiman Tukiman (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2021)
This study aims to determine the implementation of the policy of an integrative child social welfare center in Jombang Regency. The research method used is a qualitative descriptive method using George Charles Edward's theory of policy implementation, which consists of several variables that affect the success of a policy implementation, including communication, resource sources, disposition, and the structure of the brokerage. The result that Dieh found in this research is that the implementation is less than optimal. In the aspect of communication, socialization has not been carried out to the community and the communication that has been carried out has not been optimally carried out to internal implementers. In the aspect of resources, it was found that there was a lack of staff resources. In the aspect of disposition, it was found that the understanding of implementers regarding policies was not the same. And in the aspect of the bureaucratic structure, it was found that the Standard Operating Procedure (SOP) has not been resolved as a policy implementation guideline.